Design and development of a multi-criteria program accreditation dashboard information system - Widiyanto, Widiyanto; Wahyuningsih, Sri Suharmini; Majidah, Majidah; Sutartono, Sutartono (Edukasi, 2023)
The presence of Independent Accreditation Institutions requires study programs to adapt the accreditation process. Each Independent Accreditation Institution has different accreditation instruments. Previously, many information systems have been developed to facilitate the management of study program accreditation documents. With the existence of Independent Accreditation Institutions, it is necessary to develop a system that was previously using accreditation instruments from BAN-PT, which must now be adapted to the accreditation instruments of the Independent Accreditation Institutions. Therefore, a system was designed that can modify or add accreditation instruments to the system by users without the need for hard coding. The method used in the development of the information system uses the System Development Life Cycle (SDLC). SDLC consists of initial investigation, system analysis, system design, system development, system implementation, and system maintenance. From the results of system testing, the system has been able to meet the needs in accreditation management with standard criteria that can be adapted to user needs.